Microbubble PhoXonic resonators: Chaos transition and transfer. (January 2022) - Rosello-Mecho, Xavier; Frigenti, Gabriele; Farnesi, Daniele; Delgado-Pinar, Martina; Andrés, Miguel V.; Ratto, Fulvio; Conti, Gualtiero Nunzi; Soria, Silvia
Highlights: PhoXonic Resonators. Chaos transfer. Graphical abstract: Abstract: We report the activation of optomechanical chaotic oscillations in microbubble resonators (MBRs) through a blue-side excitation of its optical resonances. We confirm the sequence of quasi-periodical oscillation, spectral continuum and aperiodic motion; as well as the transition to chaos without external feedback or modulation of the laser source. In particular, quasi periodic transitions and a spectral continuum are reported for MBRs with diameters up to 600 µm, whereas only an abrupt transition into a spectral continuum is observed for larger microbubbles.